2018
DOI: 10.1108/jme-12-2016-0063
|View full text |Cite
|
Sign up to set email alerts
|

Black leaders matter

Abstract: Purpose The purpose of this study is to evaluate factors that contribute to black male school leaders’ career progression and sustenance within the teaching profession. This, because the progression of black and minority ethnic (BME) teachers in Britain has been the subject of much debate. Fewer BME teachers are in leadership roles in education, and there are only 230 BME headteachers of approximately 24,000 primary and secondary headteachers. Design/methodology/approach The headteachers’ professional lives … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 16 publications
0
11
0
Order By: Relevance
“…The lack of representation of women, particularly women of color, in formal leadership roles across education is an ongoing concern (Mirza, 2008;Fuller, 2017;Miller and Callender, 2018;Manfredi et al, 2019). Improving the visibility of women's leadership, in education and beyond, is one way that visual practitioners can highlight the contributions made by, and the barriers facing, women and seek to counter depictions that exclude, undermine, objectify, and misrepresent.…”
Section: Representing Women's Leadership In Educationmentioning
confidence: 99%
“…The lack of representation of women, particularly women of color, in formal leadership roles across education is an ongoing concern (Mirza, 2008;Fuller, 2017;Miller and Callender, 2018;Manfredi et al, 2019). Improving the visibility of women's leadership, in education and beyond, is one way that visual practitioners can highlight the contributions made by, and the barriers facing, women and seek to counter depictions that exclude, undermine, objectify, and misrepresent.…”
Section: Representing Women's Leadership In Educationmentioning
confidence: 99%
“…Network capital, positive work role models, and prior life experiences have also been found to predict entrepreneurial intention, agency perspective, and agency behavior (Niehaus & O'Meara, 2015;Tolentino et al, 2014). Some researchers caution that organizational subcultures that entail inherent gender or racial bias can either limit personal agency or fuel agentic behavior (Afioni & Karam, 2019;Miller & Callender, 2018). On a theoretical level, job crafting suggests that workers should be empowered to alter their work tasks and relationships to align their personal sense of calling or meaning with their work goals (Berg et al, 2013;.…”
Section: Background Literature and Definitionsmentioning
confidence: 99%
“…Racial /ethnic discrimination (Bush et al, 2006) were also been found to be a barrier in the progression of teachers of BAME heritage. Furthermore, Lumby and Coleman (2007) found race/ ethnicity was a barrier to the progression of teachers of BAME heritage, a situation they reconfirmed a decade later in 2017 (See, Lumby and Coleman, 2017), and supported by Miller and Callender (2018).…”
Section: Barriers To Progressionmentioning
confidence: 99%